Validating and expanding a framework of a triple bottom line dominant logic for business sustainability through time and across contexts. Issue 1 (7th January 2019) - Ferro, Carlos; Padin, Carmen; Høgevold, Nils; Svensson, Göran; Sosa Varela, Juan Carlos
Abstract : Purpose: The purpose of this paper is to validate or refute the previous empirical findings of a TBL dominant logic for business sustainability and to expand the TBL dominant logic for business sustainability with additional dimensions and items. The study aims to provide bottom-up-based multi-dimensional framework in relation to the sustainable development goals (SDG) of the UN 2030 agenda for sustainable development. Design/methodology/approach: Key corporate informants in top Spanish companies were requested to participate in the study. A total of 89 usable questionnaires were returned, generating an initial response rate of 42.4%. Findings: A framework for a TBL-dominant logic in the context of business sustainability has been empirically tested successfully across contexts and through time, thus providing substantiation for universal applicability. Research limitations/implications: This study provides a relevant and important substantiation for validity and reliability across contexts and through time. It is important in research to establish a theoretical framework at the corporate level for business sustainability in connection with SDGs. This study is not without its limitations, but offers opportunities for further research. Practical implications: The framework provides practitioners with a foundation to assess their efforts at business sustainability, taking into account a broad selection of aspects across environmental, social and economic elements that contribute to SDGs. Originality/value: This study makes two relevant and valuable contributions to developing a framework of TBL dominant logic for business sustainability, namely, validation and expansion. It offers also multiple opportunities for both research and practice to assess business sustainability efforts across environmental, social and economic aspects in relation to SDGs.